2019
DOI: 10.1038/s41598-019-48816-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and functional analyses of 3D placental extravillous trophoblast spheroids

Abstract: Placental extravillous trophoblast (EVT) invasion is essential in establishing proper blood supply to the fetus during pregnancy. However, traditional 2D in vitro systems do not model the in vivo invasion process in an anatomically-relevant manner. Our objectives were to develop a 3D spheroid model that would allow better emulation of placental invasion in vitro and to characterize the transcriptomic and functional outcomes. HTR8/SVneo EVT ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Moreover, such cells can increase the destruction of cytotrophoblasts ( Yang et al, 2019 ). The reduced number of cytotrophoblasts that were invaded cannot sufficiently modify the SA ( Stenqvist et al, 2013 , Wong et al, 2019 ). Based on placental histology, FasL expression was lower than cytochrome c expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such cells can increase the destruction of cytotrophoblasts ( Yang et al, 2019 ). The reduced number of cytotrophoblasts that were invaded cannot sufficiently modify the SA ( Stenqvist et al, 2013 , Wong et al, 2019 ). Based on placental histology, FasL expression was lower than cytochrome c expression.…”
Section: Discussionmentioning
confidence: 99%
“…This gives them an edge over 2D monolayers and helps them better mimic the heterogenous environment found in vivo. 76,77 Recent studies support the use of microsensors in the standardization of growth patterns and investigation of various pathways that occur in vivo using 3D cultures. Microsensors are advantageous in gauging the transient effects which do not require cellular markers to evaluate thus providing the experimenter information beyond what one gathers from an array of optical imaging tools and microscopy.…”
Section: Software Usedmentioning
confidence: 99%
“…The potential to maintain different types of cells within the same population can be attributed to the design of the 3D spheroid, owing to the varying depths at which the cells are located from oxygen and nutrient sources. This gives them an edge over 2D monolayers and helps them better mimic the heterogenous environment found in vivo 76,77 …”
Section: Techniques and Devices For Analyzing 3d Culturesmentioning
confidence: 99%
“…White et al showed a placental spheroid system using JAr cells in 1988 [ 65 ]. Also, Wong et al used the HTR-8/SVneo extravillous trophoblast cell line to create a spheroid model to show placental invasion [ 66 ]. Spheroid systems are the simplest of 3D in vitro systems to set up and can be useful for drug discovery, as they provide a more realistic and physiologically relevant model than 2D in vitro assays.…”
Section: In Vitro Placental Modelsmentioning
confidence: 99%